2020
DOI: 10.1016/bs.vh.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin/vasopressin-like neuropeptide signaling in insects

Abstract: The origin of the oxytocin (OT)/vasopressin (VP) signaling system is thought to date back more than 600 million years. OT/VP-like peptides have been identified in numerous invertebrate phyla, including molluscs, annelids, nematodes and insects. However, to date, we only have a limited understanding of the biological role(s) of this GPCR-mediated signaling system in insects. This chapter presents the current knowledge of OT/VP-like neuropeptide signaling in insects by providing a brief overview of insect OT/VP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Due to the structural similarity of the ligands and the high sequence homology of the receptors, there is some crossreactivity between them. In vitro and in vivo studies have demonstrated that oxytocin receptor can form heterodimers with V2R [43,44], although the physiological relevance of the association of oxytocin receptor with V2R remains to be determined. Interestingly, in human myometrium, oxytocin activates the Rho-ROCK pathway to phosphorylate the regulatory subunit of MLC, leading to contractions [45,46] and vasopressin can also induce uterine contractions [47].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the structural similarity of the ligands and the high sequence homology of the receptors, there is some crossreactivity between them. In vitro and in vivo studies have demonstrated that oxytocin receptor can form heterodimers with V2R [43,44], although the physiological relevance of the association of oxytocin receptor with V2R remains to be determined. Interestingly, in human myometrium, oxytocin activates the Rho-ROCK pathway to phosphorylate the regulatory subunit of MLC, leading to contractions [45,46] and vasopressin can also induce uterine contractions [47].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of vasopressin, a similar nonapeptide with only two amino acid differences from OXT, is extremely similar to that of OXT. Oxytocin receptor (OXTR), which together with the related V1a, V1b, and V2 vasopressin receptor subtypes form a subfamily of the large G protein-coupled receptor superfamily, is the sole receptor for OXT that is currently known [82].…”
Section: Neuroprotective Properties Of Oxytocinmentioning
confidence: 99%
“…For example, oxytocin and vasopressin can influence aggression in both sexes, yet there is not a consistent link between either peptide, the sex it acts in, and the expression of aggression across vertebrate species (SI Table 1). However, while the sex-specificity and functions of oxytocin/vasopressin are well-understood, insects only possess a single homolog of oxytocin/vasopressin (15)(16)(17)(18), providing a unique opportunity to determine how the observed functions of the duplicates (oxytocin/vasopressin) are influenced by a single homolog (inotocin). We particularly focus on the function of inotocin in males and females, as oxytocin/vasopressin are known to show sex-specificity in their function across vertebra taxa (SI Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…A single copy homologue of the oxytocin/vasopressin system - inotocin – exists in insects [16, 17]. While inotocin has been broadly associated with some social contexts in insects [17-19], it is unclear whether it has been specifically co-opted to influence parental care behaviors as most insects do not show elaborate care of their offspring with prolonged parent-offspring associations as observed in vertebrates. There are exceptions, notably burying beetles in the genus Nicrophorus where parents not only have extended associations with their offspring, they also directly provision food to their offspring by regurgitating digested carrion [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation